POWDER FOR METAL LAMINATE MOLDING WITH Cr2N POWDER MIXED IN STAINLESS STEEL POWDER

By mixing Cr2N powder with stainless steel powder in specific concentrations and particle size ranges, the flowability and filling properties of stainless steel metal powders for additive manufacturing are significantly improved, addressing molding defects and enhancing product quality.

JP2025043196APending Publication Date: 2025-03-28SANYO SPECIAL STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023150582
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Stainless steel metal powders used in three-dimensional metal additive manufacturing often suffer from molding defects such as voids due to inadequate flowability and filling properties, despite the use of gas atomized powders with high spherical shape.

Method used

The addition of Cr2N powder to stainless steel powder, specifically in the range of 0.3 to 10.5 mass%, where the particle diameter D10 of the Cr2N powder is between 4.0 to 15.0 μm, significantly improves the flowability and filling properties of the stainless steel metal powder.

Benefits of technology

The incorporation of Cr2N powder enhances the flowability and filling properties of stainless steel metal powders, reducing molding defects and producing high-quality additive manufacturing products with improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043196000001_ABST
    Figure 2025043196000001_ABST
Patent Text Reader

Abstract

To provide stainless steel metal powder for metal laminate molding, which exhibits excellent flowability or filling property.SOLUTION: Powder for metal laminate molding has Cr2N powder mixed in stainless steel powder. Particularly, for the Cr2N powder to be mixed, D10 which is a particle size of a cumulative volume of 10% satisfies 4.0-15.0 μm, and the amount of mixed Cr2N powder is 0.3-10.5 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stainless steel-based metal powder suitable for the rapid melting and rapid solidification process of three-dimensional metal additive manufacturing. [Background technology]

[0002] In recent years, metal additive manufacturing technology has become widespread, making it possible to manufacture a variety of complex parts in near-net shapes. Stainless steel, in particular, is widely used among Fe-based materials because it is less susceptible to molding cracks and has excellent mechanical properties and corrosion resistance.

[0003] However, it is known that metal additive manufacturing is more prone to defects such as voids than conventional processes. To reduce defects, it is effective to use powder with excellent fluidity and packing properties. Although powder with high sphericity produced by gas atomization is generally used, this is still insufficient, and gas atomized powders with even better fluidity and packing properties are required.

[0004] One possible approach to improve the fluidity of gas atomized powder is to mix it with ceramic powder to reduce the adhesive force between metal particles.

[0005] For example, there has been a report of an example in which ceramic powders (BN, TiB2, SiC, WC) were added to an Fe-based powder with 0.03%≦C≦0.80%, 0.01%≦Si≦2.50%, 0.10%≦Mn≦8.00%, P≦0.10%, S≦0.02%, Al≦0.1%, N≦0.1%, and O≦0.5%, and metal additive manufacturing was performed using an electron beam or laser (see Patent Document 1).

[0006] However, in Patent Document 1, ceramic powder is added for the purpose of improving tensile strength and Young's modulus, and no consideration is given to what particle size of ceramic powder should be added to improve the fluidity of the mixed powder. In addition, the ceramic powder contains elements such as W, B, and Ti that are not contained in the Fe-based powder of the counterpart material, and there is a concern that the impurity elements may deteriorate the mechanical properties of the shaped body. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 7306601 Summary of the Invention [Problem to be solved by the invention]

[0008] The problem that the present invention aims to solve is to provide a stainless steel-based metal powder for metal additive manufacturing that has excellent fluidity or filling properties, and further to provide a stainless steel-based metal powder for metal additive manufacturing that has excellent fluidity or filling properties. [Means for solving the problem]

[0009] The inventors have found that stainless steel powder mixed with Cr2N powder, in particular stainless steel-based metal powder for metal additive manufacturing in which stainless steel powder is mixed with 0.3 to 10.5 mass% Cr2N powder having a D10 of 4.0 to 15.0 μm, has excellent fluidity and filling properties, and is suitable for metal additive manufacturing.

[0010] Therefore, the first means for solving the problems of the present invention is a powder for metal additive manufacturing in which stainless steel powder is mixed with Cr2N powder.

[0011] A second aspect is the powder for metal additive manufacturing according to the first aspect, characterized in that the particle diameter D10 of the mixed Cr2N powder at 10% cumulative volume satisfies 4.0 to 15.0 μm.

[0012] A third aspect is the powder for metal additive manufacturing according to any one of the first and second aspects, characterized in that the amount of the mixed Cr2N powder is 0.3 to 10.5 mass %. Effect of the Invention

[0013] By the above means, the addition of nitrides consisting of Cr and N, which are components contained in stainless steel, has less adverse effects than increasing the components of impurity elements in stainless steel and can improve fluidity or packing properties, so that an excellent powder for metal additive manufacturing with improved fluidity or packing properties compared to stainless steel alone can be obtained. Since the Cr2N powder mixed with stainless steel has a D10 value within a predetermined range to obtain a suitably fine powder, the particle size of the Cr2N powder particles is smaller than the particle size of the stainless steel powder, and the Cr2N powder particles fill the voids in the stainless steel powder particles, improving packing properties. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a graph showing fluidity with the fluidity on the vertical axis and Cr2N on the horizontal axis. [Diagram 2] FIG. 2 is a graph showing packing property with apparent density on the vertical axis and Cr2N on the horizontal axis. [Diagram 3] FIG. 3 is a graph showing packing property with tap density on the vertical axis and Cr2N on the horizontal axis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Prior to describing preferred embodiments of the present invention, the materials to be mixed into the powder for metal additive manufacturing, the mixing procedure, the manufacturing procedure, etc. will be appropriately described below. Note that the percentage of the powder blend amount refers to mass%.

[0016] [Stainless Steel Powder] In the powder for metal additive manufacturing in the present invention, the stainless steel powder is a powder that determines its basic characteristics, and stainless steel such as austenitic, ferritic, martensitic, and precipitation hardening types can be appropriately selected and used depending on the application scene of the additive manufacturing body. In the examples, SUS316L steel and SUS630 steel of the Japanese Industrial Standards (JIS) are described as examples, but are not limited to these. For example, other stainless steel powders such as JIS SUS430 steel, SUS447J1 steel, SUS403 steel, SUS420J2 steel, SUS440A steel, SUS301 steel, SUS304 steel, SUS304L steel, SUS316 steel, SUS310S steel, SUS321 steel, SUS347 steel, SUS329J1 steel, and SUS631 steel can be mentioned.

[0017] In view of the flowability and packing properties, the stainless steel powder is preferably a gas atomized powder produced by a gas atomization method that is likely to produce excellent spherical shapes.

[0018] The average particle size D50 (volume average) of the stainless steel powder is preferably 10 to 100 μm, more preferably 30 to 50 μm, and even more preferably 35 to 45 μm.

[0019] [Cr2N powder] The method for producing the Cr2N powder is not particularly limited, and any known method may be used. The reason why the Cr2N powder was selected as the powder to be mixed with the stainless steel is that Cr and N are elements generally contained in stainless steel, and therefore, they are unlikely to adversely affect the mechanical properties of the stainless steel additive manufacturing body as impurities.

[0020] The particle size D10 of the Cr2N powder at 10% of its cumulative volume is preferably 4.0 to 15.0 μm. By adding Cr2N powder that satisfies 4.0μm≦D10≦15.0μm to stainless steel powder, the fine Cr2N powder particles can reduce the adhesive force between the stainless steel powder particles, improving the flowability. Also, when the particle size of the added Cr2N powder particles is smaller than that of the stainless steel powder, the Cr2N powder particles fill the gaps between the stainless steel powder particles, improving the filling property.

[0021] Since the amount of fine Cr2N powder particles is reflected in D10, the smaller D10, the greater the amount of fine Cr2N powder particles. If the D10 of the Cr2N powder is smaller than 4.0, the excessively added fine Cr2N powder particles will aggregate with each other, causing the fluidity of the mixed powder to deteriorate. If the D10 of the Cr2N powder particles is larger than 15.0, the amount of fine Cr2N powder particles is small, so the adhesive force between the stainless steel powder particles cannot be sufficiently reduced, and the fluidity cannot be sufficiently improved. Therefore, the D10 of the Cr2N powder is preferably 4.0 to 15.0 μm, more preferably 5.0 to 12.0 μm, and more preferably 6.0 to 10.0 μm or less.

[0022] Furthermore, D50, which is the particle size of 50% cumulative volume of the Cr2N powder, is preferably 10.0 to 20.0 μm, and more preferably 12.0 to 18.0 μm.

[0023] Furthermore, D90, which is the particle size of 90% of the cumulative volume of the Cr2N powder, is preferably 25.0 to 40.0 μm, and more preferably 27.0 to 33.0 μm.

[0024] [mixture] The stainless steel powder and the Cr2N powder can be mixed by a V-mixer, a tumbler mixer, a bowl mixer, or other suitable equipment, or can be mixed by hand in a container.

[0025] Regarding the amount of Cr2N powder mixed with the stainless steel powder, it is preferable to mix 0.3 to 10.5% by mass of Cr2N powder in the metal additive manufacturing powder in order to obtain a powder with excellent fluidity and packing. From the viewpoint of improving fluidity and packing, the amount of Cr2N powder mixed is preferably 0.3% or more by mass, more preferably 0.7% or more, and even more preferably 1.0% or more. On the other hand, since it is not desirable to add an excessive amount to the stainless steel powder, and even if the amount is too large, the fluidity is not necessarily improved, the amount of Cr2N powder mixed is preferably 10.5% or less by mass, more preferably 7.7% or less, and even more preferably 5.8% or less.

[0026] [molding] The method for producing a molded object using the powder for metal additive manufacturing of the present invention includes a rapid melting and rapid solidification process, which is a process of melting and solidifying a metal powder. Specific examples of this process include a three-dimensional additive manufacturing method, a thermal spraying method, a laser coating method, and a build-up method. In particular, stainless steel, which is the main component of the powder for metal additive manufacturing of the present invention, is suitable for a three-dimensional additive manufacturing method using a powder bed fusion bonding method, and can form a large-sized molded object at a high density.

[0027] Therefore, for example, a 3D printer can be used as a three-dimensional additive manufacturing method using the powder for additive manufacturing of the present invention. In the powder bed fusion method (powder bed method) among additive manufacturing methods, a laser beam or an electron beam is irradiated to the powder for additive manufacturing of the present invention that is spread. By the irradiation, the particles are rapidly heated and melted. The melted particles are then rapidly solidified. This melting and solidification causes the particles to bond to each other. Irradiation is selectively performed on a part of the powder for additive manufacturing that is spread. The part of the powder that is not irradiated does not melt. A bonding layer is formed only in the irradiated part.

[0028] A thin layer of Fe-based alloy powder is then spread over the bonding layer. A laser beam or electron beam is irradiated onto some of the stainless steel powder. The irradiation causes the particles to melt rapidly. The molten particles then rapidly solidify. This melting and solidification bonds the particles in the powder together, forming a new bonding layer. The new bonding layer also bonds with the existing bonding layer.

[0029] By repeating the bonding by irradiation, the aggregate of bonding layers gradually grows. This growth results in a three-dimensional object. This additive manufacturing method makes it easy to obtain objects with complex shapes. EXAMPLES

[0030] [Stainless Steel Powder] In the examples, stainless steel powders of SUS316L steel and SUS630 steel specified in the Japanese Industrial Standards (JIS) were used. Gas atomized powder was produced by vacuum melting inert gas atomization method, and then classified with a -63μm sieve to produce stainless steel powder with excellent sphericity and cleanliness.

[0031] [Cr2N powder] In the examples, Cr2N powder (Nippon Shinkinzoku Mfg., product name: Cr2N-O) was used. For comparison, Cr2N powder with different particle sizes was prepared by air classifying the purchased Cr2N powder and used for mixing.

[0032] [mixture] The stainless steel powder and the Cr2N powder were mixed using a V-type mixer. The comparative example with 0% Cr2N powder is an example where no Cr2N powder was mixed.

[0033] [Particle size measurement] The particle sizes D10, D50, and D90 are measured based on volume. The total volume of the powder is taken as 100%, and a cumulative curve is obtained. The particle size at the point on this curve where the cumulative volume is 50% is D50 (similarly, D10 and D90 are the particle sizes at the points where the cumulative volume is 10% and 90%). The particle sizes D10, D50, and D90 are measured by the laser diffraction scattering method. An example of a device suitable for this measurement is the Microtrac MT3000 laser diffraction / scattering particle size distribution analyzer from Nikkiso Co., Ltd. The powder is poured into the cell of this device together with pure water, and the particle size is detected based on the light scattering information of the particles.

[0034] [Flow rate measurement] The flow rate of the mixed powder was measured and the flow rate of the metal powder was confirmed based on JIS Z 2502. It is evaluated by opening the orifice at the bottom of a funnel containing 50 g of a metal powder sample and measuring the time (s / 50 g) required for 50 g of powder to fall from the funnel. A shorter time required indicates excellent flowability.

[0035] [Measurement of apparent density] The apparent density of the mixed powder was measured based on JIS Z2504 "Metal powder - Apparent density measurement method." Using a funnel with a specified orifice diameter and funnel angle, the powder was poured into a non-magnetic cup of a specified size v, and the cup was filled. After scraping it flat with a non-magnetic horizontal spatula, the mass m was weighed and the value calculated as m / v was calculated.

[0036] [Measurement of tap density] Tap density is measured according to the JIS Z2512 standard, and is calculated by dividing 50 g of powder by 100 cm 3 The mixture was filled into a cylinder and dropped from a height of 10 mm with 200 taps to evaluate the packing density. That is, the measurement conditions are as follows: Drop height: 10mm Tap count: 200 It is.

[0037] The particle size of the Cr2N powder, the particle size of the stainless steel powder, the amount of Cr2N mixed into the stainless steel powder, the fluidity, the apparent density, and the tap density are shown in Table 1 for the examples and in Table 2 for the comparative examples.

[0038] The fluidity and filling property were evaluated from the following viewpoints. When the fluidity is 18.0s / 50g or more, it is judged to have poor fluidity and is indicated by underlining in the table. When the apparent density does not meet the standard for each stainless steel material, it is determined that the filling ability is poor, and this is indicated by underlining in the table. SUS316L: (apparent density) ≧4.05g / cm 3 , SUS630: (apparent density) ≧3.85g / cm 3 . If the tap density does not meet the standard for each SUS material, it is deemed to have poor filling properties and is underlined in the table. SUS316L: (Tap density) ≧4.65g / cm 3 , SUS630: (Tap density) ≧4.45g / cm 3 .

[0039] [Table 1]

[0040] [Table 2]

[0041] Based on the results of Tables 1 and 2, the relationship between the fluidity, apparent density, tap density, and the amount of Cr2N powder added is shown in graphs in Figures 1 to 3. As shown in Figures 1 to 3, the fluidity, apparent density, and tap density were all poor when Cr2N powder was not added. It was also found that as the amount of Cr2N powder increased, the filling rate improved, but the fluidity tended to decrease. It was also confirmed that even when the same amount of Cr2N powder was added, the fluidity changed significantly depending on the size of the powder, and the filling rate also differed depending on the particle size.

[0042] It was confirmed that all of Examples 1 to 7 of the present invention, in which Cr2N powder was mixed, had excellent flowability and packing properties, and were suitable as powders for metal additive manufacturing. That is, the flow rates of Examples 1 to 7 were 15.0 to 16.8 s / 50 g, which indicates that the flow rates are excellent. The apparent density of SUS316L in Examples 1 to 6 is 4.10 g / cm 3 and their tap density is 4.71 g / cm 3 From the above, it was confirmed that the mixed powders of Examples 1 to 6 were excellent in packing ability. The apparent density of SUS630 in Example 7 is 4.01 g / cm 3 and the tap density is 4.52 g / cm 3 Therefore, it was confirmed that the mixed powder of Example 7 was excellent in packing ability.

[0043] Comparative Example 1 is a SUS316L stainless steel powder with no CrN powder mixed in, and has a flow rate of 18.1s / 50g and an apparent density of 4.02g / cm 3 , tap density is 4.62g / cm 3 In comparison, it can be seen that the fluidity and filling property are improved by mixing the Cr2N powder of the present invention. Comparative Example 5 is a SUS630 stainless steel powder with no CrN powder mixed in, and has a flowability of 18.3 s / 50 g and an apparent density of 3.82 g / cm 3 , tap density is 4.33g / cm 3In comparison, it can be seen that the fluidity and filling property are improved by mixing the Cr2N powder of the present invention.

[0044] In Comparative Example 2, the Cr2N powder had a small D10 value and was too fine, so that although the filling property was improved, no improvement in flowability was observed. In Comparative Example 3, the D10 value of the Cr2N powder was large and the amount of fine powder in the Cr2N powder was small compared to the stainless steel powder, so no improvement in fluidity was observed. In Comparative Example 4, a large amount of Cr2N powder was added to the stainless steel powder, and as a result, no improvement in fluidity was observed. [Industrial Applicability]

[0045] The mixed powder of stainless steel powder and Cr2N powder according to the present invention can be used as a stainless steel-based metal powder for metal additive manufacturing, which has excellent formability.

Claims

【Request 1】 Stainless steel powder with Cr 2 Powder for metal additive manufacturing mixed with N powder. 【Request 2】 Mixed Cr 2 The powder for metal additive manufacturing according to claim 1, characterized in that the N powder has a particle diameter D10 of 4.0 to 15.0 μm, which is a particle diameter at 10% cumulative volume. 【Request 3】 Mixed Cr 2 The powder for metal additive manufacturing according to claim 1 or 2, characterized in that the amount of N powder is 0.3 to 10.5 mass%.

Citation Information

Patent Citations

  • Layered object and manufacturing method thereof

    JP7306601B1